Modelling swell propagation across the Pacific - Pathirana, Sachini; Young, Ian; Meucci, Alberto (Frontiers in Marine Science, 2023)
Ocean wave swell generated in the vicinity of Campbell Island in the Southern Ocean is tracked along Great Circle paths across the Pacific Ocean. Data from a wave buoy at Campbell Island provides data on the directional spectrum in the generation region. The swell is measured at locations along a series of 19 Great Circle paths across the Pacific using Sentinel-1 SAR and CFOSAT satellite data. The WAVEWATCH III spectral wave model is used as a diagnostic tool to investigate the physical processes active in the swell propagation and decay. The results indicate that present day spectral wave models over-estimate the decay rate of swell. Although these models contain source terms to represent swell decay and negative wind input, these terms still largely remain tuning parameters. The data indicates that further research is required to adequately represent the observed magnitudes of the swell decay. In addition, the data show that currents have only a small impact on the observed swell decay and that islands can have a major impact. Such island impacts are poorly represented by spectral wave models.